2013
DOI: 10.1016/j.jvs.2013.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and lower extremity amputation risk in nonelderly diabetic patients

Abstract: Objective To examine the association between use of statin and non-statin cholesterol-lowering medications and risk of nontraumatic major lower-extremity amputations (LEA) and treatment failure (LEA or death). Design of Study A retrospective cohort of patients with Type I and Type 2 diabetes mellitus (diabetes) was followed for five years between 2004 and 2008. The follow-up exposure duration was divided into 90-day periods. Use of cholesterol-lowering agents, diabetic medications, hemoglobin A1c, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
1
27
1
1
Order By: Relevance
“…[8][9][10] Multiple studies have shown that statin use is associated with lower rates of LEA. 11,12 No association between statin therapy and mortality has been shown in LEA patients. In 2013 the American College of Cardiology (ACC) and the American Heart Association (AHA) released guidelines on the "Treatment of Blood Cholesterol to Reduce Atherosclerotic Cardiovascular Risk in Adults."…”
mentioning
confidence: 99%
“…[8][9][10] Multiple studies have shown that statin use is associated with lower rates of LEA. 11,12 No association between statin therapy and mortality has been shown in LEA patients. In 2013 the American College of Cardiology (ACC) and the American Heart Association (AHA) released guidelines on the "Treatment of Blood Cholesterol to Reduce Atherosclerotic Cardiovascular Risk in Adults."…”
mentioning
confidence: 99%
“…In addition, several studies in recent years have shown that statins improved pain-free walking distance, anklebrachial index values and treadmill exercise time [8,36]. Although Dosluoglu et al [37] did not find a favorable statins effect on long-term stent or bypass patency and limb salvage, Sohn et al [38] reported that compared with patients who did not use cholesterollowering agents statin users were 35-43% less likely to experience lower extremity amputation. In this study, users of other cholesterol-lowering medications were not significantly different in terms of leg amputation risk [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although Dosluoglu et al [37] did not find a favorable statins effect on long-term stent or bypass patency and limb salvage, Sohn et al [38] reported that compared with patients who did not use cholesterollowering agents statin users were 35-43% less likely to experience lower extremity amputation. In this study, users of other cholesterol-lowering medications were not significantly different in terms of leg amputation risk [38]. Moreover, in another study, statin-treated patients with PAD after endovascular intervention had significantly higher rates of primary patency at 24 months (43% vs 33%), secondary patency (66% vs 51%), limb salvage (83% vs 62%), and overall survival (77% vs 62%) [39].…”
Section: Discussionmentioning
confidence: 99%
“…These murine data support that this network of metabolic impairments activates detrimental feed-forward cycles of local and systemic oxidative stress and dysregulated energy homeostasis with local mitochondrial dysfunction and inflammation, thus resulting in neural injury and DPN. Corroborating this idea, there are some clinical studies showing that dyslipidemiais strongly correlated with DPN [2,87] and that lowering cholesterol, not glycemia, is significantly associated with decreasing lower-extremity amputations among patients with diabetes [2,88].…”
Section: Figure 2 A-fmentioning
confidence: 98%